Individual Relationship Analysis: A Phenomenon of Using Instagram Second Account - Della Giska Meidiani; Maulina Larasati Putri; Vera Wijayanti Sutjipto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The rapid advancement of technology has significantly transformed the way individuals communicate, particularly through social media platforms. These platforms, often referred to as part of cyberspace, have facilitated seamless and widespread interpersonal interaction. Social media has become a space where various forms of social activity are displayed, including the phenomenon of self-presentation or